Pengaruh Organizational Culture dan Motivation terhadap Employee Performance pada RSUD Soreang Kabupaten Bandung - Rizki Chrisulianti; Raihan Ula Hanifah (Institut Manajemen Wiyata Indonesia, 2019)
This study aims to determine: (1) The influence of organizational culture on employee performance, (2) the influence of motivation on employee performance, and (3) The effect of organizational culture and motivation on employee performance. The subjects of this study were some of the employees of Soreang Hospital in Bandung. The number of sampel is 100 respondent. The sampel selection tehnique used was purposive sampling. Methods of data collection through surveys using questionnaires. Technical quality testing tools include test of validity and reliability, classical analysis and descriptive analysis using the SPSS program. The results show that (1) Organizational culture has no effect on employee performance. (2) Motivation positively affects employee performance. 3) Organizational culture and motivation positively affect employee performance. Further research is needed by this RSUD so that employees are able to produce high performance.